Cause or Function? On the 19th-Century Revolution in the theory of Value and its Consequences to Contemporary Economics - Appelt, Katarzyna (Studia Oeconomica Posnaniensia, 2017)
A 19th-century revolution in the theory of value did change both an understanding and an approach to the concept of value. However, as Taylor [1958] noticed, a fundamental change in the theory of value was not subjectivism but a concept of utility and a notion of interdependence. As a result, contemporary schools of economics such as neoclassical and mathematical ones recognize the economic phenomena as a functional adequacy. The article proves that giving up the causal thinking for functional adequacy may generate adverse effects/results in science. Functional adequacy does not explain the nature of phenomena. It resolves in fact to the scientific description. Moreover, it has been noticed that the followers of the positivism school recognize interdependence relations not referring to value theory which is a fundamental element of the theory of prices. In addition, it has been stressed that resigning from causal thinking may lead to the logical fallacy called circulusvitiosus. Functional adequacy does not include a category of time which is a basic category in exchange relations.